Staying and performing: How human resource management practices increase job embeddedness and performance - Tian, Amy; Cordery, J.; Gamble, J. (-, 2016)
Purpose – The purpose of this paper is to empirically examine the effect of human resource management (HRM) practices on employees’ organisational job embeddedness and job performance. Following the ability-motivation-opportunity (AMO) model of HRM, the authors predicted that ability-, motivation- and opportunity-enhancing HRM practices would relate to fit, links and sacrifice components of job embeddedness, with these components mediating the relationship between HRM and employee job performance. Design/methodology/approach – Data were collected from a matched sample of 197 Chinese state-own firm employees and their supervisors. Multiple mediation test was used to test direct and mediating effects. Findings – Results indicated that HRM practices contribute to the creation and development of embeddedness, and the improvement of job performance. The job embeddedness components of fit, links and sacrifice were found to mediate the HRM-job performance relationship. The results suggest that organisations can proactively enhance both embeddedness and employee performance through implementing appropriate HRM practices. Research limitations/implications – While this study makes a contribution to the understanding of the relationship between HRM practices, employees’ organisational job embeddedness, the authors collected most of the data during one time period. Originality/value – Directly addressing these theoretical and methodological issues, the study makes two key contributions to the HRM and job embeddedness literatures. First, the authors found that the HR practices will directly influence employees’ job embeddedness. Second, the authors extend the scope of the AMO framework of HR by proposing that job embeddedness dimensions as important mediators in the HRM-job performance relationship.